2005
DOI: 10.1016/j.micres.2004.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Diffusible and volatile compounds produced by an antagonistic Bacillus subtilis strain cause structural deformations in pathogenic fungi in vitro

Abstract: An efficient antagonistic strain of Bacillus subtilis, originally isolated from the rhizosphere of established tea bushes, was found to cause structural deformities in six pathogenic fungi under in vitro culture conditions. This effect was attributed to the production of diffusible and volatile antifungal compounds. Out of the selected test fungi four were phytopathogenic, while the remaining two were of clinical importance. The bacterial strain successfully restricted the growth of all test fungi in dual cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 14 publications
15
127
0
11
Order By: Relevance
“…[11][12][13] Organic compounds such as allyl alcohol inhibit germination of S. sclerotiorum, benzothiazole, cyclohexanol, n-decanal, dimethyl trisulfide, 2-ethyl-1-hexanol and nonanal of pseudomonades inhibit mycel growth of S. sclerotiorum, or not further identified compounds of B. subtilis caused structural deformations of pathogenic fungi. 8,14,15 Our survey supports and extends the previous observations that rhizobacteria produce biologically relevant organic volatile compounds. Beside pseudomonades and B. subtilis particularly potent volatiles are emitted by Serratia odorifera, S. plymuthica, Stenotrophomonas maltophilia, S. rhizophila and Burkholderia cepacia.…”
Section: Discussionsupporting
confidence: 87%
“…[11][12][13] Organic compounds such as allyl alcohol inhibit germination of S. sclerotiorum, benzothiazole, cyclohexanol, n-decanal, dimethyl trisulfide, 2-ethyl-1-hexanol and nonanal of pseudomonades inhibit mycel growth of S. sclerotiorum, or not further identified compounds of B. subtilis caused structural deformations of pathogenic fungi. 8,14,15 Our survey supports and extends the previous observations that rhizobacteria produce biologically relevant organic volatile compounds. Beside pseudomonades and B. subtilis particularly potent volatiles are emitted by Serratia odorifera, S. plymuthica, Stenotrophomonas maltophilia, S. rhizophila and Burkholderia cepacia.…”
Section: Discussionsupporting
confidence: 87%
“…Studies in various ecological niches have indicated that the relative proportion of different microbes and dominance of a particular group of microorganism (species or strains) depend upon various environmental factors. The soils of temperate and alpine climates have been reported dominated by species of Bacillus and Pseudomonas [10,14]. Specifi c protocols must be followed to identify locally adapted benefi cial microbes according to their tolerance to environmental stresses, soil types and crop under consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Biocontrol properties of the bacterium Production of diffusible and volatile antifungal compounds by the bacterium was evaluated following dual cultures using standard methods as described in Chaurasia et al [10] using Alternaria alternata (ITCC 4215) and Fusarium oxysporum (ITCC 4219) as test isolates. Reduction in fungal biomass was determined in broth assays [11].…”
Section: Solubilization Of Tricalcium Phosphate (Tcp) and Production mentioning
confidence: 99%
“…Antimicrobial compounds are produced in either volatile or nonvolatile forms (Brooks et al, 1994;Cazar et al, 2005;Chanway, 1996;Chaurasia et al, 2005). The nonvolatile compounds are often detected using simple plate assay (Chaurasia et al, 2005) and the filtrates can be easily extracted, purified and characterized (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%